Hydrogen peroxide signaling via its transformation to a stereospecific alkyl hydroperoxide that escapes reductive inactivation - Raphael F. Queiroz (Nature Portfolio, 2021)
A major question in redox signaling is how H2O2 oxidizes target protein thiols in the presence of glutathione peroxidases and peroxiredoxins. We reveal signaling by H2O2 via its enzymatic conversion to an alkyl hydroperoxide that stereo-specifically escapes peroxidases and oxidizes target proteins.